Pengaruh Pemberian Sayur Pepaya Muda (Carica Papaya L) terhadap Volume Asi pada Ibu Menyusui di RT 24 Kelurahan Thehok Kota Jambi Tahun 2022 - Lidya Kurniasari; Dewi Junita Lamtumiar; Nia Nurzia (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
According to WHO data. worldwide coverage of exclusive breastfeeding is only around 36% during the 2007-2014 period. Based on data from UNICEF as many as 136.7 million babies were born worldwide and only 32.6% of them were exclusively breastfed in the first 6 months. Papaya fruit (Carica papaya L) is a fruit that contains Lactagogum which is a substance that can increase and increase milk production. The purpose of this study was to analyze the effect of giving young papaya vegetables (Carica papaya L) to the volume of breast milk in nursing mothers in the RT 24 Thehok Jambi City 2022. The type of this research is quantitative with the design used is pre-experimental one group pretest posttes. The population in this study were all breastfeeding mothers with a sample of 11 respondents. The statistical test used was paired T-test.The results obtained by the average milk production in nursing mothers (pretest) is 16.55. While the average milk production in nursing mothers (posttest) is 21.18. The P value = 0.00 is smaller than 0.05 which is Ha which means that there is an influence of giving young papaya (Carica papaya L) to the volume of breast milk for breastfeeding mothers in the Work Area of RT 24 Kelurahan Thehok Jambi City 2022. The results of this study are expected young papaya vegetables (Carica papaya L) can be used by the community, especially in nursing mothers because can increase the volume of breast milk.